A semi-supervised method to generate a persian dataset for suggestion classification. - Safari, Leila; Mohammady, Zanyar (Language Resources & Evaluation, 2024)
Suggestion mining has become a popular subject in the field of natural language processing (NLP) that is useful in areas like a service/product improvement. The purpose of this study is to provide an automated machine learning (ML) based approach to extract suggestions from Persian text. In this research, first, a novel two-step semi-supervised method has been proposed to generate a Persian dataset called ParsSugg, which is then used in the automatic classification of the user's suggestions. The first step is manual labeling of data based on a proposed guideline, followed by a data augmentation phase. In the second step, using pre-trained Persian Bidirectional Encoder Representations from Transformers (ParsBERT) as a classifier and the data from the previous step, more data were labeled. The performance of various ML models, including Support Vector Machine (SVM), Random Forest (RF), Convolutional Neural Networks (CNN), Long Short Term Memory (LSTM), and the ParsBERT language model has been examined on the generated dataset. The F-score value of 97.27 for ParsBERT and about 94.5 for SVM and CNN classifiers were obtained for the suggestion class which is a promising result as the first research on suggestion classification on Persian texts. Also, the proposed guideline can be used for other NLP tasks, and the generated dataset can be used in other suggestion classification tasks.